PENGARUH HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DALAM MENINGKATKAN PENJUALAN (STUDI KASUS PADA UD RATNA CAKE & COOKIES) - Ahmad Bairizki (Valid: Jurnal Ilmiah, 2017)
This study aims to determine the effect of price, promotion, and product quality on purchasing decisions of cakes at UD Ratna Cake & Cookies as well as to obtain information about the variables that have the most dominant influence on the purchase decision. This type of research is associative, while the technique of collecting data is through observation and interviews with questionnaires as an instrument. Data analysis was first conducted to test the validity and reliability of the instrument, followed by a classic assumption test including normality test, heteroscedasticity and multicollinearity. Then performed multiple linear regression analysis, t test and F test to determine the truth of the hypothesis and is followed by the analysis of the coefficient of determination.The results of multiple linear regression analysis showed the following equation Y = 0.354 + 0,230X₁ + 0,184X₂ + 0,517X₃. These results suggest that price, promotion and product quality have influence on purchase decisions. Based on t test results obtained at the price variable t <t table (1.698 <1.985) so it is said that the price variable (X₁) had no significant effect on the purchase decision variable (Y). On promotion variable results obtained t count> t table (2.022> 1.985) so it is said that the promotion variable (X₂) has a significant influence on purchase decision variable (Y). On quality product variable, it obtained by the t count> t table (4.085> 1.985) so it is said that the variable of product quality (X₃) has a significant influence on variable of purchase decisions (Y). Then based on the F test results obtained F count> F table (32.627> 14.475), which means that the real level of 5%, the price variable (X₁), promotion (X₂), and product quality (X₃) simultaneously have a significant influence on the purchase decision variabel (Y). Through coefficient test of determination (R²) obtained the value of Adjusted R Square of 50.2%. It means 50.2% variable purchase decisions are influenced by three independent variables which are price, promotion and product quality and the balance of 49.8 influenced enumerated by other variables which not included in this study.